Development of a program for the prediction of placement of spacecraft based on TLE data (International Journal of Mathematics and Physics, 2023)
Abstract. Based on the archive of the TLE data of the spacecraft, the placements of the Low Earth Orbit spacecraft (Аl-Farabi-2), Medium Earth Orbit spacecraft (BEIDOU-3 M20), and High Earth Orbit spacecraft (IPM 2 & BREEZE-M R/B) were predicted in coordinate form using the first set of TLE data and SGP4/SDP4 model in Python. The placements of the spacecraft were also predicted by using the STK software. The actual placements of the above spacecraft were obtained by directly parsing their archive of TLE data, and the errors of the two prediction methods were calculated. Subsequently, the errors were compared, and the similarity of error and prediction accuracy of the two prediction methods were evaluated, allowing for an analysis of the feasibility of predicting spacecraft placements through a Python program.